A class of generalized uniform asymptotic expansions - Wilson C. Obi (International Journal of Mathematics and Mathematical Sciences)
In [1] E. L. Reiss obtained a multivariable expansion of the problem L[y]≡y″+2ϵy′+y=0, t>0;y(0;ϵ)=0, y′(0,ϵ)=1 by means of a technique which does not employ the traditional method of using a secularity condition in obtaining higher order approximations. In this paper Reiss' technique is formalized and new results are established.